1981
DOI: 10.1111/j.1440-1681.1981.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Calcium for Contraction of Guinea‐pig Isolated Tracheal Smooth Muscle

Abstract: 1. Contractile responses of guinea-pig tracheal smooth muscle to KCl, histamine, acetylcholine and prostaglandins were reduced after the removal of extracellular Ca2+ from the bathing medium. 2. KCl-induced contractures were more dependent on extracellular Ca2+ than acetylcholine-induced responses, but less so than histamine-induced contractures. 3. Responses to high concentrations of contractile agents were less dependent on extracellular Ca2+ than those to low concentrations. 4. Repeated additions of histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 10 publications
(7 reference statements)
3
24
0
Order By: Relevance
“…Some workers (Creese & Denborough, 1981;Cerrina et al, 1982) have reported that tracheal spasm induced by K+ was more readily suppressed by Ca2+ deprivation than spasm evoked by acetylcholine. They therefore proposed that K+-induced spasm of trachealis is primarily dependent on the cellular influx of Ca2+ while acetylcholine may rather act to promote the release of Ca2+ from intracellular sites.…”
Section: Intracellularelectrophysiological Recordingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some workers (Creese & Denborough, 1981;Cerrina et al, 1982) have reported that tracheal spasm induced by K+ was more readily suppressed by Ca2+ deprivation than spasm evoked by acetylcholine. They therefore proposed that K+-induced spasm of trachealis is primarily dependent on the cellular influx of Ca2+ while acetylcholine may rather act to promote the release of Ca2+ from intracellular sites.…”
Section: Intracellularelectrophysiological Recordingmentioning
confidence: 99%
“…In the trachealis of the ox (Kirkpatrick, Jenkinson & Cameron, 1975), dog (Farley & Miles, 1975) and guinea-pig (Creese & Denborough, 1981;Cerrina, Renier, Floch, Duroux & Advenier, 1982) removal of Ca2+ from the bathing medium markedly suppresses spasm evoked by K+. Some workers (Creese & Denborough, 1981;Cerrina et al, 1982) have reported that tracheal spasm induced by K+ was more readily suppressed by Ca2+ deprivation than spasm evoked by acetylcholine.…”
Section: Intracellularelectrophysiological Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, prolonged exposure to EGTA may not only affect the residual extracellular calcium ions, it may also remove calcium from the intracellular stores. In the present study, the protocol described by Creese & Denborough (1981) The contraction induced by the addition of endothelin to the organ baths was extremely slow in onset. Its prolonged nature was similar to the contraction which results from the application of leukotrienes to isolated bronchial tissue (Hanna et al, 1981).…”
Section: Autoradiographic Studiesmentioning
confidence: 99%
“…More recently a new subtype, the EP4 receptor, has been described (Coleman et al, 1994a). EPI receptors are present in smooth muscles, mediate a contractile response (Lawrence et al, 1992;Sheldrick et al, 1988), and have been shown to be coupled to phosphoinositide hydrolysis through regulatory G proteins (Creese & Denborough, 1981). There are selective agonists for the EPI receptor but none is highly selective, while several specific antagonists have been developed (Coleman et al., British Journal of Pharmacology (1996) 118,[1597][1598][1599][1600][1601][1602][1603][1604] A.i.…”
Section: Introductionmentioning
confidence: 99%